Tinjauan Hukum terhadap Strategi Penanganan Keamanan Maritim Perbatasan Wilayah Laut dan Dampaknya pada Aspek Pertahanan Keamanan - Pandoe, Ridha Munawir Masly; Sumantri, Siswo Hadi; Suwarno, Panji; Widodo, Pujo (LITERATUS, 2024)
Indonesia is geographically very strategically located between two oceans and two continents, so that the Indonesian maritime region is a very important sea route for global trade highways and national and international sea traffic. Indonesia with this position and potential has a considerable opportunity to become a maritime country based on natural resources. This potential can be a strength as well as a challenge with a high level of vulnerability and can disrupt security stability which can threaten the integrity of the Unitary State of the Republic of Indonesia (NKRI). The research method used is a normative research method which will later bring up new arguments, the results of the study found that the conditions in which Indonesia became a maritime country made it a lot of crime threats to Indonesia's maritime sovereignty. This position must be supported by a strong defense and security system and changing the pattern of national development which is not only oriented towards the land dimension but also oriented towards the sea dimension. To that end, several policies and regulations have been established, but until now these regulations are still sectoral, resulting in disharmony and overlapping regulations and authorities in marine security. This also applies to the law enforcement system and state sovereignty at sea, which is influenced by these laws and regulations.